Factors influencing female sexual dysfunction, gestational stage in South America and Asia, systematic review in the last decade - Rivera-Felix, Lauro Marcoantonio (2021)
Introduction: Female sexual dysfunction (FSD) is defined as a disorder in desire, arousal, orgasm and/or pain during sexual intercourse, which generates personal stress and has an impact on quality of life, in the present systematic review, it is describe the factors that most influence female sexual dysfunction during the gestational stage. Objective: To analyze the articles published on the factors that influence female sexual dysfunction during the gestational stage in South America and Asia in the last decade. Materials and Methods: A systematic review of articles indexed in the following databases was carried out: Doaj, Nure, Pubmed, Scopus, Scielo, Medigraphic, Maternal-fetal health journal and finally the Science, teaching and technology article. Results: There are a variety of factors that influence female sexual dysfunction during pregnancy, the most frequent being the advancement of the gestation trimesters, typical of the pregnancy itself, due to fears of complications or beliefs, the emotional state, and the style of life that the pregnant woman leads. Conclusions: There are various factors by which this change in sexual behavior occurs, to avoid female sexual dysfunction in the gestational stage, so it is recommended that the pregnant woman receive appropriate professional guidance on the changes and difficulties in sexuality that it will be given in this period.